Online dating applications and risk of youth victimization: A lifestyle exposure perspective - Kaakinen Markus; Koivula Aki; Savolainen Iina; Sirola Anu; Mikkola Marko; Zych Izabela; Paek Hye-Jin; Oksanen Atte (Wiley, 2022)
Based on lifestyle exposure theory (LET), this study examined online dating application (ODA) use and victimization experiences among adolescents using large cross-national samples of Finnish, American, Spanish, and South Korean young people between ages 15 and 18. According to logistic regression analyses in two substudies, ODA use was associated with more likely victimization to online harassment, online sexual harassment, and other cybercrimes and sexual victimization by adults and peers. According to mediation analyses, this relationship was mainly accounted for by the fact that ODA users engage in more risky activities in online communication and information sharing. Attention should be paid to the risks ODAs pose to vulnerable groups, such as young people, with insufficient skills to regulate their social relationships online.